Permanent education as a tool for the prevention of infections related to health care (Research, Society and Development, 2020)
Introduction: Permanent Health Education (EPS) is a strategic tool for improving processes in the work environment, which facilitates the expansion of knowledge based on the work context. Infections related to health care - (HAI) are associated with important unfavorable outcomes in the work process, which has a connection with professional training, and with the low awareness of health professionals in face of this which is one of the major causes of injuries to patient health. Objectives: Investigate in databases the permanent education in health as a tool for the prevention of infections related to health care (IRAS). Method: This is a descriptive research with a qualitative approach, carried out in the virtual health library, in the databases Medline, Lilacs and Bdenf, in the period between February and June of two thousand and nineteen, with a five-year time frame, in the English and Portuguese. Results: Health professionals still do not have depth in EPS to develop it in an appropriate way, which has an perspective on EPS of professional training and not a significant construction of knowledge together for the work process. Final considerations: EP is an important tool for the work process in health services because it seeks to solve the problems inherent in the work practice, thus promoting the creation of alternatives to solve the problems in order to promote a lively work in the work environment. realizing that to achieve qualified assistance, it is necessary that adherence to patient safety practices is a focus of health professionals.